Population, poverty and the future of India - Karan Singh (New Delhi, 1975)
The National Institute of Family Planning is happy to present to the general public, and specially those interested in the family planning programme in India, this compilation of some of the speeches of Dr. Karan Singh. As Union Minister of Health and Family Planning he has lifted the program me from the clinics to which it had been relegated and placed it in its proper perspective as part of a multi pronged assault on the citadels of poverty. He has stressed the necessity to involve all sections of society in family planning. It is his thesis, and also the accepted policy of the Government of India, that the family planning programme must become a mass movement embodying in it the people's urges and aspirations for a better life and their efforts to attain it.
Keywords: Poverty